Coronary Artery Spasm During Pulsed Field vs Radiofrequency Catheter Ablation of the Mitral Isthmus - Zhang, Chi; Neuzil, Petr; Petru, Jan; Funasako, Moritoshi; Hala, Pavel; Kopriva, Karel; Koruth, Jacob S; Dukkipati, Srinivas R; Reddy, Vivek Y (JAMA cardiology, 2024)
IMPORTANCE: In treating atrial fibrillation, pulsed field ablation (PFA) is a novel energy modality with comparable efficacy to conventional thermal ablation, such as radiofrequency ablation (RFA), but with the benefit of some preferentiality to myocardial tissue ablation. Studies have demonstrated important safety advantages, including the absence of esophageal injury or pulmonary vein stenosis and only rare phrenic nerve injury. However, there is emerging evidence of coronary artery vasospasm provoked by PFA. OBJECTIVE: To compare the incidence and severity of left circumflex arterial vasospasm between PFA and RFA during adjacent ablation along the mitral isthmus. DESIGN, SETTING, AND PARTICIPANTS: This prospective cohort study enrolled consecutive adult patients receiving first-ever PFA or RFA of the mitral isthmus during catheter ablation of atrial fibrillation in 2022 with acute follow-up at a single referral European center. EXPOSURE: A posterolateral mitral isthmus line was created using either a multielectrode pentaspline PFA catheter (endocardial ablation) or a saline-irrigated RFA catheter. Simultaneous diagnostic coronary angiography was performed before, during, and after catheter ablation. Nitroglycerin was planned for spasm persisting beyond 20 minutes or for significant electrocardiographic changes. MAIN OUTCOMES AND MEASURES: The frequency and severity of left circumflex arterial vasospasm was assessed and monitored, as were time to remission and any need for nitroglycerin administration. RESULTS: Of 26 included patients, 19 (73%) were male, and the mean (SD) age was 65.5 (9.3) years. Patients underwent either PFA (n = 17) or RFA (n = 9) along the mitral isthmus. Coronary spasm was observed in 7 of 17 patients (41.2%) undergoing PFA: in 7 of 9 (77.8%) when the mitral isthmus ablation line was situated superiorly and in 0 of 8 when situated inferiorly. Conversely, coronary spasm did not occur in any of the 9 patients undergoing RFA. Of 5 patients in whom crossover PFA was performed after RFA failed to achieve conduction block, coronary spasm occurred in 3 (60%). Most instances of spasm (9 of 10 [90%]) were subclinical, with 2 (20%) requiring nitroglycerin administration. The median (range) time to resolution of spasm was 5 (5-25) minutes. CONCLUSION AND RELEVANCE: When creating a mitral isthmus ablation line during catheter ablation of atrial fibrillation, adjacent left circumflex arterial vasospasm frequently occurred with PFA and not RFA but was typically subclinical.
Keywords: Humans; Coronary Vasospasm; Female; Aged; dospělí; Nitroglycerin; senioři; lidé; Atrial Fibrillation; koronární vazospasmus; Heart Atria; katetrizační ablace; Adult; ženské pohlaví; Male; srdeční síně; mužské pohlaví; nitroglycerin; prospektivní studie; Catheter Ablation; fibrilace síní; Prospective Studies